Polímeros autocicatrizantes para aplicações biomédicas: uma revisão bibliográfica - Veiga, Augusto da (Universidade Federal de São Carlos, 2024)
Intelligent materials, which change their characteristics according to external stimuli, have been increasingly researched as alternatives to traditional materials. Among them, self-healing materials already had great space in structural applications, adhesives, and coatings, particularly ceramics and polymers. The latter have advantages over other classes of materials, notably their versatility of processing and applications. With the increase of the necessity for regenerative medicine and the demand for materials with less environmental impact, biomedical applications have also become a major focus of self-healing polymers. Shape-memory effect polymers, hydrogels, among others, are examples of the applied materials, mainly in the areas of tissue engineering, biosensors, smart wound-dressings, and drug delivery. This ensures a more efficient, and much less invasive treatment, especially thinking about complicated treatments such as cancer, bone, heart problems, among others. In addition, polymers also allow production by additive manufacturing, which ensures individuality for each patient, in addition to less waste, which can bring several advantages. These are the reasons why this theme presents several possibilities and has been increasingly researched. In the meantime, the present work seeks to point out the state of the art of the application of self-healing polymers for biomedical application, focusing on the production by 3D and 4D prints.
Self-healing polymers for biomedical applications: a literature review
Keywords: Polímeros; Autocicatrização; Biomédica; Manufatura aditiva; Impressão 3D; Polymers; Self-healing; Biomedical; Additive manufacturing; 3D printing; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA